ASSESSMENT OF THE DEMOGRAPHIC SITUATION AND RESETTLEMENT OF SYUNIK FROM A NATIONAL SECURITY PERSPECTIVE - Manasyan, Maxim; Gspoyan, Grisha (Crisis Management and Technologies, 2023)
The article presents the specifics and changes in the demographic and resettlement situation of Syunik, which is of crucial strategic importance for the Republic of Armenia, on the basis of facts. The existing problems of the spheres of demography and resettlement assessed from the point of view of national security have been identified. The main directions of the demographic policy to be implemented by state in Syunik are given in the article. The most important way to improve the settlement and demographic situation in Syunik is considered to be the concentration and settlement of Artsakh internally displaced people (IDPs) in some cities and rural settlements of the region. This will also provide an opportunity to preserve the Artsakh community and cultural and ethnographic identity.